Meconium-stained amniotic fluid: a risk factor for postpartum hemorrhage - Bouchè C; Wiesenfeld U; Ronfani L; Simeone R; Bogatti P; Skerk K; Ricci G (Dove Medical Press, 2018)
Carlo Bouchè,1 Uri Wiesenfeld,1 Luca Ronfani,1 Roberto Simeone,2 Paolo Bogatti,1 Kristina Skerk,1 Giuseppe Ricci1,2 1Institute for Maternal and Child Health, IRCCS Burlo Garofolo, Trieste, Italy; 2Department of Medicine, Surgery and Health Sciences, University of Trieste, Trieste, Italy Background/aim: Clinical data with respect to the impact of meconium on the risk of maternal hemorrhage are scarce. Therefore, in this study, we aimed to determine whether meconium-stained amniotic fluid (MSAF) represents a risk factor for postpartum hemorrhage (PPH) after vaginal delivery in a large unselected population. Patients and methods: A retrospective cohort study evaluated 78,542 consecutive women who had a vaginal delivery between 24th and 44th weeks of gestation. The women who had undergone cesarean section were excluded to avoid possible bias. Postpartum blood loss was measured with graduated blood sack. Postpartum blood loss between 1,000 and 2,000 mL and >2,000 mL were classified as moderate and severe PPH, respectively. Results: A total of 74,144 patients were available for analysis. According to the color of amniotic fluid (AF), two groups of patients were identified: MSAF (n=10,997) and clear AF (n=63,147). The rates of severe and massive PPH were found to be significantly higher in the MSAF group than that of clear AF group (OR=1.3, 95% CI: 1.2–1.5, p<0.001 and OR=2.5, 95% CI: 1.5–4.2, p<0.001). Operative vaginal delivery rate was found to be higher in the MSAF group than that of clear AF group, but the difference was only borderline significant (OR=1.5, 95% CI: 1.0–2.2, p=0.05). There were no significant differences between the MSAF and the clear AF groups with respect to episiotomies, second- or third-degree perineal tears, vaginal–perineal thrombus, cervical lacerations, vaginal births after cesarean section, twin deliveries, and placental retention rates. Conclusion: To the best of our knowledge, this is the first clinical study that has investigated the role of MSAF as a risk factor for PPH after vaginal delivery in an unselected population. Our results suggest that MSAF is significantly associated with higher risk of moderate and severe PPH than clear AF. Keywords: amniotic fluid, delivery complications, meconium, postpartum hemorrhage